Stochastic algorithm for search an optimal trajectory of an automatic manipulator - A.V., Fedossova; Santoyo, Julian (Revista Colombiana de Computación, 2007)
Is presented the stochastic outer approximations algorithm for robot trajectory planning. Initially, it is had an automatic manipulator of three degrees of freedom. Keywords: outer approximations methods, semi-infinite programming.